The Effectiveness Online Learning toward Students’ Motivation at FKIP University of Riau - M. Yogi Riyantama Isjoni; Filma Alia Sari; Mifta Rizka (STAI Hubbulwathan Duri, 2022)
At this time the world is shocked by the outbreak of a disease caused by a virus called corona or better known as Covid-19 (Corona Virus diseases-19). This policy has a major impact on the wheels of human life, one of which has an impact in the field of higher education Especially in FKIP students of Riau University. This study aims to analyze the effect of the effectiveness of online learning as a result of covid-19 on student learning motivation in the FKIP environment of Riau University.This study was conducted to show the effect of the effectiveness of online learning on student motivation at FKIP Riau University. The Methodology in this study is a quantitative approach with multiple linear reggresions models. The sample is 615 student at FKIP Riau University. The research instrument was a closed questionnaire based on likert using google form. Hypothesis testing using t test dan f test. The results showed that learning effectiveness had a positive and significant effect of 75.4%. These results illustrate that during Covid-19 pandemic, online learning was effectively carried out in order to increase student learning motivation.